DETERMINANTS OF ENTREPRENEURIAL PLANNING ABILITY (STUDY OF CAUSALITY IN BIOLOGY DEPARTMENT STUDENTS STATE UNIVERSITAS NEGERI MEDAN) - herkules herkules; Syahmi Edi; Amalia Akita (Sean Institute, 2023)
Entrepreneurship education in universities is very important for its role today, especially in strengthening the mindset, fostering interest and the ability to compile entrepreneurial planning. Moreover, in the biology department, which incidentally rarely understands the concept of entrepreneurship, it is necessary to strengthen the ability to compile entrepreneurial planning. Therefore, this study aims to analyze the determinants of entrepreneurial planning ability in biology students. This research is a quantitative research survey method with a cross sectional design. The sample of this study was 90 students who took entrepreneurship courses. Data analysis using logistic regression tests. The results showed that knowledge (p =0.007) and the presence of entrepreneurial companions (p=0.001) affected the entrepreneurial planning ability of students majoring in biology. Universities in addition to developing entrepreneurship courses practically, must also be able to provide mentors for students to discuss the business plan they will run.